2014
DOI: 10.1177/0003489414551980
|View full text |Cite
|
Sign up to set email alerts
|

Voice Outcomes After Endoscopic Treatment of Laryngotracheal Stenosis

Abstract: Following endoscopic management of stenosis, those with PGS have poorer voice outcomes compared to those with SGS/TS. The majority of those with SGS/TS are not dysphonic. Vocal outcomes are greatest for those with stenosis beginning at least 2 cm distal to the vocal folds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Additionally, patient‐reported voice‐related quality of life improved postdilation in patients with SGS versus other stenoses of the airway. Similar findings were observed by Hatcher et al Unfortunately, dilation procedures are not long‐lasting; many patients have to return within 1 to 2 years for repeated procedures. In some cases, multiple dilations result in a lengthier period of airway patency, but this result varies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, patient‐reported voice‐related quality of life improved postdilation in patients with SGS versus other stenoses of the airway. Similar findings were observed by Hatcher et al Unfortunately, dilation procedures are not long‐lasting; many patients have to return within 1 to 2 years for repeated procedures. In some cases, multiple dilations result in a lengthier period of airway patency, but this result varies.…”
Section: Discussionmentioning
confidence: 99%
“…413 A few studies 46 have retrospectively demonstrated improved voice QOL after endoscopic balloon dilation in patients with LTS. None of the published studies evaluating voice outcomes in LTS have been prospective.…”
mentioning
confidence: 99%
“…Of note, no statistically significant difference was observed for FEV 1 /FVC, which is primarily utilized in the evaluation of lower as opposed to upper airway obstruction 23 . Patient reported outcomes, as measured by V‐RQOL, 24 VHI‐10, 25 CCQ, 26 have also been studied in the setting of endoscopic treatment for laryngotracheal stenosis. Using these measures, our iSGS cohort also shows significant postoperative improvement.…”
Section: Discussionmentioning
confidence: 99%